Resource Allocation for Economic Development - Chenery, Hollis B.; Kretschmer, Kenneth S. (Econometrica, 1956)
The primary purpose of this study is to develop a model based on linear programming and input-output techniques which will assist in the formulation of development programs for underdeveloped areas. I. The elements of the development problem and the data available are considered from the point of view of selecting the most significant structural relationships for a formal model. II. A nonlinear programming model is presented which is designed particularly to analyze the choice between self-sufficiency and international specialization and the resulting investment patterns under various types of restrictions. III. A method of solving the programming problem by a simple iterative procedure is suggested. It takes advantage of the structure of the matrix of activities and the limited number of primary factors involved. Convergence of the solution is demonstrated. IV. A development model for Southern Italy is constructed for purposes of illustration, based on studies of consumption, investment, and input structure and assumptions as to the remaining parameters. A solution for a hypothetical development program is given, showing the method of solution and the effect of variation in several of the parameters. V. The implications of the results for the solution of a more general model are considered. The relationship of the interindustry model to sector analyses and the